2020
DOI: 10.3389/fpsyg.2020.00039
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Emergent Literacy in Children With Hearing Loss

Abstract: Long-term literacy outcomes for children with hearing loss, particularly those with severeto-profound deafness who are fitted with cochlear implants (CIs) lag behind those of children with normal hearing (NH). The causes for these long-term deficits are not fully clear, though differences in auditory access between children who use CIs and those with NH may be a partial cause. This paper briefly reviews the emergent literacy model as proposed by Whitehurst and Lonigan (1998). We then examine the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 121 publications
(174 reference statements)
0
13
0
1
Order By: Relevance
“…Later in development, vocabulary knowledge and phonological abilities show a positive association such that school-age children-both those with and without hearing loss-who have higher levels of vocabulary knowledge also demonstrate enhanced phonological awareness skills (Dillon et al, 2012;Lund et al, 2015). Of particular import for children with hearing loss, who exhibit delays in developing sensitivity to phonological structure, is whether the acquisition of higher-level language constructs, including vocabulary and morphosyntax, can proceed independently of phonological development (Ingvalson et al, 2020). The current results…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Later in development, vocabulary knowledge and phonological abilities show a positive association such that school-age children-both those with and without hearing loss-who have higher levels of vocabulary knowledge also demonstrate enhanced phonological awareness skills (Dillon et al, 2012;Lund et al, 2015). Of particular import for children with hearing loss, who exhibit delays in developing sensitivity to phonological structure, is whether the acquisition of higher-level language constructs, including vocabulary and morphosyntax, can proceed independently of phonological development (Ingvalson et al, 2020). The current results…”
mentioning
confidence: 51%
“…Consistent with previous work, we found strong associations between the number of unique phonemes children produced and children's language abilities suggesting that the richness of children's phonemic production may serve as an index of their overall language ability. Individual differences in children's phonemic repertoires, the number of unique phonemes they have acquired overall, are potent predictors of literacy skills (Ingvalson et al, 2020;Wagner et al, 1997). Children with hearing loss exhibit smaller (Blamey et al, 2001;Serry & Blamey, 1999;Stoel-Gammon, 1988) izations that exhibited significantly less phonemic diversity than the speech-related vocalizations of their typically hearing peers.…”
Section: Hearing Status Phoneme Production and Language Abilitiesmentioning
confidence: 99%
“…A lthough hearing aids (HAs) and cochlear implants (CIs) can ameliorate the effects of hearing loss (HL; e.g., Waltzman et al, 2002), children with HL are a heterogeneous group-particularly with respect to their language development. Many children with HL lag behind their typically hearing (TH) peers' language development (Ganek et al, 2012;Lund, 2016;Nittrouer et al, 2018;Nott et al, 2009), which can have cascading consequences for their cognitive, social, and educational outcomes (Bat-Chava & Deignan, 2001;Briscoe et al, 2001;Ingvalson et al, 2020;Nittrouer et al, 2012). Additionally, there are differences in the visual attention (Hoffman et al, 2018) and attention coordination (Chen et al, 2020) of children with HL relative to those who are TH-skills that are tightly coupled with language development in TH children (Macroy-Higgins & Montemarano, 2016;Yee et al, 2012;Yoshida et al, 2011;Yu & Smith, 2012).…”
mentioning
confidence: 99%
“…Reading is one of the crucial skills for children to achieve academic success because much of what children need to learn is acquired through print once they reach roughly grade 4 (Chall, 1983). Research has consistently shown that the reading performance of children with hearing loss (HL) remains significantly worse than that of their hearing peers (Wauters et al, 2006;Spencer and Marschark, 2010;Cupples et al, 2014), which can hamper their success in various academic domains (Ingvalson et al, 2020). Nowadays more and more children with HL are fitted with appropriate amplification, such as hearing aid and/or cochlear implant (CI), which provides them with access to speech sounds to some extent and thus bring substantial gains in their spoken language and reading ability (Tomblin et al, 2005;Vermeulen et al, 2007;Spencer and Oleson, 2008;Niparko et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are large variations in reading outcomes among the children with HL, and some children's reading ability is even above the average grade level of their normal-hearing peers (Geers, 2003;Vermeulen et al, 2007;Geers et al, 2008). Many previous studies intended to improve reading instructions for children with HL have identified factors that contribute to reading achievements, among which phonological awareness (PA), orthographic knowledge (OK), and semantic competence (SC) are the main linguistic skills (Dillon et al, 2012;Von Muenster and Baker, 2014;Chan and Yang, 2018;Wass et al, 2019;Ingvalson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%